Religious Symbolism and the Experience of Life as Meaningful: Addition, Enhancement, or Both? - Nathaniel F. Barrett (Religions, 2023)
This paper explores the question of how religious symbolism functions to provide a more meaningful or enriched experience of life. It examines a common and highly influential view, referred to here as the “source model”, for which this function requires the addition to experience of transcendent meanings generated by rituals and other specially adapted kinds of symbolic activity. Using Robert Bellah’s Religion in Human Evolution and Clifford Geertz’s “Religion as a Cultural System” as representative examples, I critique a key premise of the source model, namely that the meaning-making function of religious symbolism evolved in response to a universal experience of life as problematic. I argue that the experience of life as problematic is a product of symbolism, not a precondition. Moreover, with respect to this experience, I propose that symbolism functions not to add meaning but to enhance meanings that are vaguely discerned in everyday life. I close with the suggestion that an enhanced experience of life as problematic is itself a kind of enriched meaning and an important source of the affective power of religious practice.